Mapping snow-algae in Antarctic Peninsula with multi-temporal satellite remote sensing data - Hashim, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
This article reports on the use of selected spectral image transform technique for detecting and mapping of snow algae growth using multi-temporal Landsat Thematic Mapper (TM), archived from early 80's to the recent Landsat-8 Operational Land Imager (OLI) acquired in March 2015. In-situ spectral radiometry samples during UTM-Antarctica summer 2015 expedition were used in air-to-ground correlation of the corresponding satellite data sets, later yield to retrieve snow algae occurrences in 2009-2015 summer. Multi-temporal analysis of the snow-vegetation growth extents extracted was then compared to against the climate-change effects of the corresponding area in Antarctic Peninsula. Hence, the indicator for snow-vegetation growth as effects of the climate-change could be inferred. Results indicated good agreement (Pearson's coefficient r=0.85, p<0.01) between snow-vegetation growth extent with the temperature changes measured in the corresponding area. Recent in-situ verification of the selected sites in the region confirmed the agreements.